Contraceptive Method Selection in Reproductive Age Couples: A Literature Review - Indria, Gita Ayu; Intarti, Wiwit Desi (Yayasan Ahmad Mansyur Nasirah, 2025)
Indonesia has the fourth-largest population in the world. Uncontrolled population growth can decrease the health status and quality of life of the population. Therefore, the government has an obligation to control the rate of population growth. One way to manage population growth is through family planning programs and the use of contraceptives by couples of reproductive age. The aim of this program is to regulate the number of births and control birth spacing. Hence, couples of reproductive age need to select appropriate contraceptive methods in order to help control population growth effectively. This study aims to examine the factors that influence couples of reproductive age in choosing contraceptive methods. The researcher used a literature review method. Relevant literature was collected from Google Scholar, comprising 10 articles published between 2020 and 2023, following the PRISMA framework. The results of the study show that there are both direct and indirect factors influencing contraceptive method selection. The direct influencing factor is the husband's support, while the indirect factors include health education and counseling, as well as the level of knowledge of couples regarding contraceptive use. It can be concluded that couples of reproductive age tend to choose appropriate contraceptive methods due to the support from their husbands, exposure to health education or having received counseling from healthcare providers, and having adequate knowledge or access to information about contraceptive tools.